IMPLEMENTASI ALGORITMA RAITA SEARCH PADA APLIKASI FILSAFAT BERBASIS ANDROID - Anggraini, Ratih; Hasibuan, Nelly Astuti; Suginam, Suginam; Waruwu, Fince Tinus (STMIK Budi Darma, 2018)
Philosophy is the search for truth through a systematic flow of thinking, meaning that conversations about everything are carried out regularly following the prevailing system so that the stages are easy to follow. Etymologically philosophy comes from English and Greek, namely